Combined healthy lifestyles and overactive bladder: a cross-sectional study of NHANES 2007–2020 - Li, Tianjie; Hou, Jian; Xiao, Bo; Li, Jianxing; Liu, Xiaodong (Frontiers in Nutrition, 2025)
ObjectivesThe relationship between adherence to a combined healthy lifestyle and the risk of overactive bladder (OAB) remains unclear. This study aimed to investigate the association between a composite healthy lifestyle score and risk of OAB in a nationally representative sample of adults.MethodsThis cross-sectional study utilized data from 20,195 non-pregnant adults aged 20–79 years in the National Health and Nutrition Examination Survey (NHANES) 2007–2020. A healthy lifestyle score was constructed based on five components: current non-smoking, low-to-moderate alcohol consumption, adequate physical activity, a healthy diet, and optimal waist circumference. OAB was defined using self-reported urinary urgency incontinence and nocturia symptoms. Weighted multivariable logistic regression models were employed to assess the association between the healthy lifestyle score and risk of OAB, adjusting for demographic, socioeconomic, and clinical covariates.ResultsAmong the 20,195 participants, 3,901 (14.58%) were identified as having OAB. A higher HLS was inversely associated with risk of OAB in a dose–response manner. Compared with individuals having 0–1 healthy lifestyle factors, those with 4–5 factors had a 46% lower risk of OAB (adjusted OR: 0.54, 95% CI: 0.45–0.65). Each additional healthy lifestyle factor was associated with a 17% lower risk of OAB (OR: 0.83, 95% CI: 0.79–0.88). Sensitivity analyses confirmed the robustness of these associations. Among individual components, non-smoking, moderate alcohol intake, regular physical activity, a healthy diet, and optimal waist circumference were each independently associated with a lower risk of OAB.ConclusionAdherence to a combination of healthy lifestyle behaviors was significantly associated with a lower risk of OAB. These findings emphasize the potential role of lifestyle-based interventions in OAB prevention and management. Given the rising prevalence of OAB, particularly in aging populations, incorporating lifestyle modifications into clinical and public health strategies may offer an effective, non-pharmacological approach to mitigating risk of OAB. Further longitudinal studies are warranted to establish causality and elucidate the underlying biological mechanisms.